O DIREITO À CONVIVÊNCIA FAMILIAR E COMUNITÁRIA: um estudo sobre o Programa Família Acolhedora na cidade de São Luís nos anos de 2012 e 2013 - Barros, Karen Beatriz Taveira (2015)
This study analyzes the Foster Care Program in São Luís, between 2012 and 2013, in the light of the provisions of the Child and Adolescent Statute, the National Plan for the Protection and Defense of the Right of Children to Family and Community life and Technical Guidelines of the CONANDA. It presents an exhibition of the historical trajectory of children and adolescents in Brazil. It discusses the right to family and community life as the effort to overcome the institutionalization of children and adolescents. It addresses the national policy of promotion and defense of family and community life and its implementation in a National Plan and child and adolescents care policy. It analyzes the Foster Care Program in São Luís, in 2012 and 2013, in its design and development. This analysis seeks to compare what is provided for in National Policy of promotion and defense of family and community life and what, indeed, has been operated in the local community through this program, at all stages, is so far the children or adolescents inserted either with respect to selected families. Thus, this study sought to investigate from the moment of reception , entry into the program , the monitoring and the departure of children , adolescents and families